'WE FEED THE NATION': BENEFITS AND CHALLENGES OF SIMULTANEOUS USE OF RESIDENT AND LONG-DISTANCE COMMUTING LABOUR IN RUSSIA’S NORTHERN HYDROCARBON INDUSTRY - Eilmsteiner-Saxinger, Gertrude (The journal of contemporary issues in business and government, 2011)
Today, the contemporary oil and gas industry in the Russian "Far North" is staffed by a mixture of a local resident workforce and long-distance commute labour. This arrangement furthers the federal geostrategic and demographic aim to keep the sub-arctic north populated, and satisfies the demand of companies to have access to a diverse and qualified labour pool. The exemplars used are the mono- industrial towns Novy Urengoy and the shift-labour camp Yamburg, which draw on the paradigm changes of northern demographic policies and labour force allocation strategies in the Soviet Union and the Russian Federation. The rich hydrocarbon deposits have created interdependency between the Russian Far North and the other regions of the Federation, not only in terms of fiscal equalisation schemes, but also because they are connected by the people who commute for work and who then invest the revenues gained from this work in the north of the country back in their home regions.